Adjusting medical school admission: Assessing interpersonal skills using situational judgement tests - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2013)
Context: Todays formal medical school admission systems often include only cognitively oriented tests, although most medical school curricula emphasise both cognitive and non-cognitive factors. Situational judgement tests (SJTs) may represent an innovative approach to the formal measurement of interpersonal skills in large groups of candidates in medical school admission processes. This study examined the validity of interpersonal video-based SJTs in relation to a variety of outcome measures. Methods: This study used a longitudinal and multiple-cohort design to examine anonymised medical school admissions and medical education data. It focused on data for the Flemish medical school admission examination between 1999 and 2002. Participants were 5444 candidates taking the medical school admission examination. Outcome measures were first-year grade point average (GPA), GPA in interpersonal communication courses, GPA in non-interpersonal courses, Bachelors degree GPA, Masters degree GPA and final-year GPA (after 7 years). For students pursuing careers in general practice, additional outcome measures (9 years after sitting examinations) included supervisor ratings and the results of an interpersonal objective structured clinical examination (OSCE), a general practice knowledge test and a case-based interview. Results: Interpersonal skills assessment carried out using SJTs had significant added value over cognitive tests for predicting interpersonal GPA throughout the curriculum, doctor performance, and performance on an OSCE and in a case-based interview. For the other outcomes, cognitive tests emerged as the better predictors. Females significantly outperformed males on the SJT (d = - 0.26). The interpersonal SJT was perceived as significantly more job-related than the cognitive tests (d = 0.55). Conclusions: Video-based SJTs as measures of procedural knowledge about interpersonal behaviour show promise as complements to cognitive examination components. The interpersonal skills training received during medical education does not negate the selection of students on the basis of interpersonal skills. Future research is needed to examine the use of SJTs in other cultures and student populations.